2018
DOI: 10.1177/1179551418759076
|View full text |Cite
|
Sign up to set email alerts
|

Graves Disease in Central Ghana: Clinical Characteristics and Associated Factors

Abstract: BackgroundGraves disease (GD) has increased in prevalence over the past decade in Africa. Despite this, the condition is not well described, especially in sub-Saharan Africa.ObjectiveWe have described the clinical characteristics and associated factors of GD in a cohort of patients attending a resource-limited setting tertiary hospital.MethodsPatients were examined thoroughly and systematically tested for the degree of clinical and biochemical thyroid status. Thyroid volume, characteristics, and blood flow wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
1
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
3
1
0
4
Order By: Relevance
“…The predominant involvement of women in the present study is in agreement with the findings documented in the literature (4,15,16). This is also consistent with the autoimmune nature of GD, as autoimmune diseases tend to affect females more than males (17).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The predominant involvement of women in the present study is in agreement with the findings documented in the literature (4,15,16). This is also consistent with the autoimmune nature of GD, as autoimmune diseases tend to affect females more than males (17).…”
Section: Discussionsupporting
confidence: 93%
“…This is also consistent with the autoimmune nature of GD, as autoimmune diseases tend to affect females more than males (17). While the females outnumbered the males in the present study, the proportion was less than that reported in the other studies (4,16). This could be the result of the improved iodine status of the population (11), following the universal iodization program and a consequent increase in the tendency for autoimmune disorders (18), which might have ultimately resulted in a lower female to male ratio.…”
Section: Discussionsupporting
confidence: 91%
“…6 Bu hastalık 30 ile 50 yaşları arasında görülmektedir. 7,8 Hastalarımızın yaş ortalaması 43,86±13,19 yıl saptanmış olup bazı çalışmalara göre yüksek olsa da Beata Jurecka-Lubieniecka ve arkadaşlarının yaptığı 709 hastayı kapsayan çalışmadaki ortalama 41,3 ± 14,27 yıl ile ve bazı başka çalışmalarla benzer bulunmuştur. 8,9 Tablo 1.…”
Section: Discussionunclassified
“…15 Sarfo-Kantanka ve ark., yaptığı 182 hastayı kapsayan bir çalışmada, çarpıntı, guatr ve nefes darlığı en sık saptanan başvuru semptomları olarak bildirilmiştir. 7 Lanas ve arkadaşlarının yaptığı başka bir çalışmada, katılan 257 hastanın %55'inin başvuru anında göz bulgusu olduğu belirtilmiştir. 9 Bizim çalışmamızda, başvuru anındaki kardiyovasküler, hipermetabolik ve göz bulgularına birçok çalışmadan farklı olarak bu kadar yüksek sıklıkta rastlanmadı, hastaların %39,76'sının asemptomatik olduğu görüldü.…”
Section: Discussionunclassified
See 1 more Smart Citation